2010
DOI: 10.1051/0004-6361/201015913
|View full text |Cite
|
Sign up to set email alerts
|

Constrained fitting of disentangled binary star spectra: application to V615 Persei in the open cluster h Persei

Abstract: Context. Using the technique of spectral disentangling, it is possible to determine the individual spectra of the components of a multiple star system from composite spectra observed at a range of orbital phases. This method has several advantages: it is unaffected by line blending, does not use template spectra, and returns individual component spectra with very high signal-to-noise ratios. Aims. The disentangled spectra of a binary star system are very well suited to spectroscopic analysis but for one proble… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…That these uncertainties are very similar could be either a coincidence, or the result of our careful selection of lines with good atomic data, resulting in a similar scatter. The renormalized disentangled spectrum of the secondary has too small a S/N to allow accurate abundance determinations, though we were able to derive its effective temperature from an optimal fit (Tamajo et al 2011) to the renormalized spectrum over the 5050-5700 Å region, albeit with much larger uncertainty than the primary. A search for the signatures of a third star in the systemʼs spectra by using SPD was negative.…”
Section: Atmospheric Parameters and Metallicity From Spectral Disentamentioning
confidence: 95%
“…That these uncertainties are very similar could be either a coincidence, or the result of our careful selection of lines with good atomic data, resulting in a similar scatter. The renormalized disentangled spectrum of the secondary has too small a S/N to allow accurate abundance determinations, though we were able to derive its effective temperature from an optimal fit (Tamajo et al 2011) to the renormalized spectrum over the 5050-5700 Å region, albeit with much larger uncertainty than the primary. A search for the signatures of a third star in the systemʼs spectra by using SPD was negative.…”
Section: Atmospheric Parameters and Metallicity From Spectral Disentamentioning
confidence: 95%
“…A genetic algorithm (GENFITT, Tamajo 2009) is used for the optimization (Tamajo et al 2011) in order to ensure that the best solution is found in a parameter space that suffers from strong degeneracies, in particular between effective temperature (T eff ) and surface gravity (log g). Table 4 compares the results of the NLTE analysis when it is run un-constrained and when the gravities of the two stars member of the eclipsing pair are fixed to the values derived by the orbital solution of Table 5.…”
Section: The Methodsmentioning
confidence: 99%
“…In OB stars, numerous oxygen, nitrogen, and silicon lines, are superimposed on the Balmer-lines are superimposed, so we carefully selected parts of their profiles that are free of such blendings as suitable for matching to theoretical line profiles. The code GENFITT has been developed to fit theoretical line profile to hydrogen lines by χ 2 minimization in T eff (Tamajo et al 2011). …”
Section: Atmospheric Analysis and Comparisonmentioning
confidence: 99%
“…In the present analysis we used a constrained optimal fitting method (Tamajo et al 2011). In the new release of the computer code for constrained optimal fitting of disentangled component spectra the following parameters can be adjusted for both stars: effective temperature, surface gravity, light dilution factor, Doppler shift, projected rotational velocity, and the vertical shift to adjust for the continuum.…”
Section: Effective Temperaturesmentioning
confidence: 99%